Induction of labour (IOL): women's satisfaction in the inpatient and outpatient settings. (18th April 2012) - Taylor-Clarke, M; Wahba, J; Touqmatchi, D; Rowland, C; Baithun, M; Akmal, S
Abstract : Ensuring a positive childbirth experience is a central feature of running a modern maternity service. Support, information and expectation all contribute to perception of care. Our aim was to compare women's experience of induction in inpatient and outpatient settings. 166 consecutive primiparous women underwent IOL with Dinoprostone 10mg retrievable pessary from October 2010 to March 2011, according to our standard protocol. Low risk women were offered outpatient IOL resulting in 80 outpatient and 86 inpatient inductions. 76 women completed a 7-item 5-point rating scale questionnaire (response rate 42% IP vs 50% OP, p=0.3). Records were reviewed for pregnancy and birth characteristics. There were no significant differences between inpatient and outpatient respondents for maternal age (p=0.3), time from induction to delivery (p=0.6), mode of delivery (p=0.1), epidural anaesthesia (p=0.3) or Apgar scores (p=0.9). Mann-Whitney U comparisons showed that both groups felt equally well informed about the induction process (p=0.7), did not feel anxious or unsupported (p=0.5) and were overall satisfied with the induction (p=0.3). Outpatient women were more likely than inpatients to consider outpatient IOL in future (p<0.05). Women who reported IOL was 'better than expected' had shorter induction to delivery intervals (T=6.5, p<0.05). There was no association between overall satisfaction and mode of delivery (Chi2=7.1;p=0.5) or use of epidural anaesthesia (Chi2=3.6;p=0.5). Satisfaction with IOL is high in risk-stratified women, independent of setting. In appropriately selected women, outpatient IOL is a positive experience that women would consider in future. Shorter induction to delivery interval is associated with more positive perception of induction.